Enhancement of the Targeting Capabilities of the Paclitaxel-Loaded Pluronic Nanoparticles with a Glycol Chitosan/Heparin Composite - Yuk, Soon Hong; Oh, Keun Sang; Cho, Sun Hang; Kim, Sang Yoon; Oh, Sangkwon; Lee, Jin Ho; Kim, Kwangmeyung; Kwon, Ick Chan (AMER CHEMICAL SOC, 2012)
An enhancement of tumor-targeting capability was demonstrated with paclitaxel (PTX)-loaded Pluronic nanoparticles (NPs) with immobilized glycol chitosan and heparin. The PTX-loaded Pluronic NPs were prepared as described in our previous report by means of a temperature-induced phase transition in a mixture of Pluronic F-68 and liquid polyethylene glycol (PEG; molecular weight: 400) containing PTX. The liquid PEG is used as the solubilizer of PTX, and Pluronic F-68 is the polymer that encapsulates the PTX. The glycol chitosan and heparin were immobilized on the surface of the Pluronic NPs in an aqueous medium, and a powdery form of the glycol chitosan/heparin immobilized Pluronic NPs (composite NPs) was obtained by freeze-drying. Field emission scanning electron microscopy and a particle size analyzer were used to observe the morphology and size distribution of the prepared NPs. To apply the composite NPs as a delivery system for the model anticancer drug PTX, the release pattern and pharmacokinetic parameters were observed, and the tumor growth was monitored by injecting the composite NPs into the tail veins of tumor-bearing mice. An enhancement of tumor-targeting capability of NPs was verified by using noninvasive live animal imaging technology to observe the time-dependent excretion profile, the in vivo biodistribution, circulation time, and the tumor-targeting capability of composite NPs.
Keywords: CANCER; THERAPEUTICS